Impact of Tax Reforms on Economic Growth of Nigeria (2000-2021) - Odukwu Victory Chika; Daniel Oshiogwemoh; Eke Promise (Goodwood Akuntansi dan Auditing Reviu, 2022)
Purpose: The objective of this study was to investigate the impact of tax reforms on economic growth of Nigeria. Methodology: This study adopted time series strategy basically concerned with how to perform impact analysis on already existing data. Secondary data were used in this study. However, relevant data for the study were obtained from Central Bank of Nigeria (CBN) Statistical Bulletins, Federal Inland Revenue Services Bulletins, and the World Bank, using judgmental sampling technique, a sample of 21 years’ period from 2000 to 2021. Regression analysis technique was used to measure the effects of the predictor variables on the criterion variables. This study used estimated technique of both descriptive statistics and Ordinary least square (OLS) regression analysis method with the help of Statistical Package for Social Sciences (SPSS 25). Results: The researcher revealed that there is a positive significant impact of VAT, CIT, & PPT on RGDP in Nigeria among other things. Therefore, the researcher established that there is a significant positive impact of tax reforms on Nigeria’s economic growth. Contribution: The study's researcher suggested that policymakers should focus on boosting the productive capacity of the economy by reforming the tax code to prioritize economic growth and opportunity, government should expand the tax yield through improved tax administration system. This is because of the danger of over-reliance on crude oil export receipts to drive the economy among other things. Limitations: One of the limitations encountered in this study is that the chosen sample size was limited to one economy in Africa which is Nigeria.